The Online PID/PIDA Simulator - Goncagül, Gökay; Hatun, Metin; Vatansever, Fahri (Fırat University, 2026)
Nowadays, computer tools are used widely in education as well as in many other fields. Especially in engineering, it is extremely important to support complex theoretical subjects with practical applications. In cases where practical applications are limited or difficult to implement, simulations are used. In this study, a new online simulator was designed for Proportional-Integral-Derivative-Acceleration (PIDA), which is the popular controller recently. The designed simulator provides online access, supporting users in comprehending the related theoretical knowledge’s and to examine the time and frequency domain system responses of the controllers individually and comparatively according to the parameters they enter. Thus, it provides both theoretical information to students and technical staff interested in this field and enables them to easily, quickly, and effectively simulate practical applications.

Günümüzde bilgisayar araçları birçok alanda olduğu gibi eğitim alanında da yaygın olarak kullanılmaktadırlar. Özellikle mühendislikte, karmaşık teorik konuların pratik uygulamalarla desteklenmesi son derece önemlidir. Pratik uygulamaların sınırlı veya zor olduğu durumlarda simülasyonlardan yararlanılmaktadır. Bu çalışmada, son zamanlarda popüler bir denetleyici olan Oransal-İntegral-Türev-İvme (PIDA) için yeni bir çevrimiçi simülatör tasarlanmıştır. Tasarlanan simülatör çevrimiçi erişim sağlayarak, kullanıcıların ilgili teorik bilgileri kavramasına ve denetleyicilerin girdikleri parametrelere göre zaman ve frekans alanı sistem tepkilerini ayrı ayrı ve karşılaştırmalı olarak incelenmesine yardımcı olmaktadır. Böylece, bu alana ilgi duyan öğrencilere ve teknik elemanlara hem teorik bilgi sunmakta hem de pratik uygulamaları kolay, hızlı ve etkili bir şekilde benzetimlerinin yapılmasını sağlamaktadır.
Çevrimiçi PID/PIDA Simülatörü
Keywords: Computer Software; Bilgisayar Yazılımı; Control Engineering; Kontrol Mühendisliği